The attainment of approximate ambidexterity in throwing and its relation to physical and mental efficiency as well as symmetry of posture - Grundlingh-Malan, Jacomi Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (B. Ed. Ph.) -- University of Stellenbosch, 1944.